2016
DOI: 10.14366/usg.15054
|View full text |Cite
|
Sign up to set email alerts
|

Hyalinizing trabecular tumor of the thyroid: diagnosis of a rare tumor using ultrasonography, cytology, and intraoperative frozen sections

Abstract: Purpose:The goal of this study was to evaluate the clinicopathological and imaging features of thyroid nodules surgically diagnosed as hyaline trabecular tumor (HTT), and to assess the role of cytology and frozen sections (FS) in the diagnosis of HTT.Methods:This study included 21 thyroid nodules in 21 patients treated from August 2005 to March 2015 (mean age, 53.3 years) who were either diagnosed as HTT or had HTT suggested as a possible diagnosis based on cytology, FS, or the final pathology report. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 18 publications
(35 reference statements)
1
23
0
Order By: Relevance
“…Hyalinizing trabecular tumors pose a challenge to diagnosis due to frequent cytological diagnosis of papillary thyroid carcinoma after FNA (919293). Several studies suggested a role for CNB in this rare thyroid tumor (9194).…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Hyalinizing trabecular tumors pose a challenge to diagnosis due to frequent cytological diagnosis of papillary thyroid carcinoma after FNA (919293). Several studies suggested a role for CNB in this rare thyroid tumor (9194).…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…In two out of three small published series investigating ultrasonographical features of HTT, the authors found that none of the patients showed any findings indicative of malignancy;13 14 in the third one, only 29% of patients showed malignant ultrasound (US) findings 15. Overall, authors described the vast majority of HTT as being solid tumours, hypoechogenic or markedly hypoechogenic 13–15…”
Section: Ultrasonographical Featuresmentioning
confidence: 99%
“…Later it was described in detail about the trabecular growth pattern and marked intratrabecular hyalinizing stroma in 1987 by Carney (Casey et al, 2004;Gupta et al, 2010;Howard et al, 2013;Jang et al, 2016;Li et al, 2012;McCarthy et al;Ninan et al, 2011;Santosh et al, 2011). Various etiological factors are put forth as; radiation exposure, arising in a background of chronic lymphocytic thyroiditis and multinodular goitre (MNG).…”
Section: Discussionmentioning
confidence: 99%
“…However the hyaline material in HTT is solid/homogenous and well defined than amyloid and not contain the streaked nuclear material as in amyloid. Cells in HTT do not have cytoplasmic granules (Gupta et al, 2010;Howard et al, 2013;Jang et al, 2016;McCarthy et al). In the present case reports, in the first case the cells showed cytoplasmic features as mentioned above, however the nuclear features were absent and hence the cells were considered as Hurthle cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation